2000
DOI: 10.1063/1.1308057
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of fully and partially coalesced lateral epitaxial overgrown GaN/sapphire (0001) by scanning thermal microscopy

Abstract: We have measured high spatial/depth resolution (∼2–3 μm) thermal conductivity (κ) at 300 K of both fully and partially coalesced GaN/sapphire (0001) samples fabricated by lateral epitaxial overgrowth. On the fully coalesced sample we found 1.86W/cm K<κ<2.05 W/cm K over a distance of approximately 50 μm. One of the partially coalesced samples had 2.00 W/cm K<κ<2.10 W/cm K on the overgrown regions, as identified by atomic force microscopy imaging. These latter results are the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(51 citation statements)
references
References 12 publications
5
46
0
Order By: Relevance
“…Concerning devices based on Group-III nitrides, sapphire, SiC, Si, and bulk GaN are used as substrates. In terms of thermal conductivity (at room temperature) SiC (6H-SiC-490 W/m × K) has a considerable advantage over the sapphire (46 W/m × K), Si (130 W/m K), and GaN (~130-200 W/m × K) substrates [1][2][3]. However, using the SiC, Si or sapphire leads to high concentration of misfit dislocations in nitride heterostructures, which can achieve magnitude of 10 8 cm -2 .…”
Section: Introductionmentioning
confidence: 99%
“…Concerning devices based on Group-III nitrides, sapphire, SiC, Si, and bulk GaN are used as substrates. In terms of thermal conductivity (at room temperature) SiC (6H-SiC-490 W/m × K) has a considerable advantage over the sapphire (46 W/m × K), Si (130 W/m K), and GaN (~130-200 W/m × K) substrates [1][2][3]. However, using the SiC, Si or sapphire leads to high concentration of misfit dislocations in nitride heterostructures, which can achieve magnitude of 10 8 cm -2 .…”
Section: Introductionmentioning
confidence: 99%
“…The experimental thermal conductivity values of GaN obtained at room temperature, using a scanning thermal microscope, are scattered in the range of 50 to 210 W/mK. 5,6) This is attributed to the effects of impurities and dislocations on the thermal properties. Luo et al 7) reported the thermal conductivity value of 155 W/mK using a third-harmonic electrical technique.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, its band gap energy is 3.4 eV at 300 K [25]. K [27]. Its breakdown field is also relatively high.…”
Section: Gallium Nitridementioning
confidence: 99%